Iron(II) and Zinc(II) Complexes with Tetradentate Bis(pyrazolyl)methane Ligands as Catalysts for the Ring‐Opening Polymerisation of rac‐Lactide. Issue 10 (15th March 2017) - Herber, Ulrich; Hegner, Katharina; Wolters, Daniel; Siris, Rita; Wrobel, Karina; Hoffmann, Alexander; Lochenie, Charles; Weber, Birgit; Kuckling, Dirk; Herres‐Pawlis, Sonja
Abstract : A new subgroup of bis(pyrazolyl)methane ligands has been developed through the synthesis of the first N, N, N, N ‐tetradentate bis(pyrazolyl)methane compounds, namely, bis(pyrazolyl)bipyridinylmethane [HC(Pz)2 Bipy, L1 ] and bis(3, 5‐methylpyrazolyl)bipyridinylmethane [HC(3, 5‐MePz)2 Bipy, L2 ]. From these ligands, a large variety of new mononuclear Fe II and Zn II complexes with counterions ranging from halides to carboxylates and sulfate were synthesised and characterised by X‐ray crystallography. The complexes [FeHC(Pz)2 BipyX2 ] (X = Cl –, CF3 CO2 –, CF3 SO3 – ), [FeHC(3, 5‐MePz)2 BipyX2 ] (X = Cl –, CF3 CO2 – ) and [ZnHC(Pz)2 BipyX2 ] (X = Cl –, CF3 CO2 – ) were tested in the melt ring‐opening polymerisation of sublimed and unsublimed technical‐grade rac ‐lactide at 150 °C. The complex [FeHC(Pz)2 Bipy(CF3 CO2 )2 ] showed the most promising results and produced a conversion of 87 % after 30 h with molecular weights of M w ≈ 30000 g mol –1 . Abstract : The first Fe II complexes with neutral ligands with catalytic activity for the ring‐opening polymerisation of lactide have been developed. Tetradentate bis(pyrazolyl)bipyridinylmethane ligands have been designed, and a series of new Fe II and Zn II complexes were synthesised.